Comparative Evaluation of Nonprocedural Nephrostomy-Related Complications in Patients with Ureteric Obstruction due to Cancer versus Other Causes: Is the Protocol of Routine 3-month Nephrostomy Exchange Optimal for Both Disease Processes? - Hu, Tianshen; Zhang, Ning; Mcdevitt, Joseph L.; Odu, Ayobami; Xi, Yin; Lamus, Daniel; Sutphin, Patrick; Kalva, Sanjeeva; Pillai, Anil K. (Journal of Clinical Interventional Radiology ISVIR, 2018)
Purpose To evaluate nonprocedural percutaneous nephrostomy (PCN) complications and assess whether the protocol of routine 3-month exchange of PCN is optimal in patients with malignant ureteral obstruction (MUO) and benign ureteral obstruction (BUO).Materials and Methods Retrospective study of 103 patients with a mean age of 48 years (36 men, 67 women) who underwent PCN placement and subsequent PCN exchanges between January 2011 and January 2014 at the institution was conducted. Comparisons of the number of catheter days for those with routine exchange and emergency exchange due to tube obstruction, infection, and mechanical failures were made in patients with MUO and BUO.Results Of the 256 PCN exchange procedures, 139 were performed in the cancer cohort and 117 in the noncancer cohort. Complications requiring emergent exchanges were more common in cancer patients, particularly due to obstruction, which accounted for 57% of exchanges in MUO with a median onset of 50 days. In contrast, the majority of noncancer patients in this study did not require emergent exchange before 3 months. Routine exchanges accounted for 43% and 55% of exchanges in MUO and BUO, respectively. In both the groups, only a small proportion of emergent tube exchanges occurred beyond 105 days.Conclusion A routine 3-month nephrostomy exchange protocol may not be ideal for all patients. The optimal timing for exchange of nephrostomy appears to be earlier for patients with MUO compared with those with BUO. A prospective study is required to define an optimal policy for postprocedural nephrostomy tube care in both the cohorts.
Keywords: nephrostomy tube exchange; malignant ureteral obstruction; benign ureteral obstruction